PENDAPATAN RUMAH TANGGA NELAYAN DI PESISIR KOTA AGUNG KABUPATEN TANGGAMUS - Sri Wahyuni; Wan Abbas Zakaria; Teguh Endaryantoindo (Lampung University, 2019)
The purpose of this research is to know the income of fisherman, structure of household income and analyze the welfare level of fishermen households in the Coastal Kota Agung. The study is conducted by survey method. The samples are taken by purposive sampling as many as 23 people. The result showed that the income of household owners and crew members was at a level of prosperity. The income of fishermen households was mostly (95.63%) from fishing businesses. Expenditures of the owner's fishermen and crew members were above the poverty line. Based on BPS criteria and poverty line, fishing boat motorbike households <5GT were in a prosperous condition. Key words : expenditures, crew, fisherman, welfare